Regarding of classification undercover investigation (search) action - Сергєєва, Д.Б (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2016)
Based on the analysis of the relevant provisions of the applicable national legislation contained in scientific sources viewpoints of scholars and practitioners, the article makes an attempt to develop a classification of secret investigative (search) actions. Established a number of problematic aspects to classify certain secret investigative (search) actions to a particular classification group. Introduction of a secret investigative (search) actions in criminal proceedings Ukraine needs further improvement of national legislation, including in the area of ​​health information, with limited access.It`s proved that secret investigative (search) actions are: audio and video surveillance; seizure of correspondence; interception of traffic Telecommunication Networks; the interception of electronic information systems; examination: publicly inaccessible places; home or other property; to establish the location of radio electronic means; observation: the person, thing or place; audio and video control locations; control of a crime in the forms of: 1) a controlled delivery, 2) controlled and operational procurement 3) investigative experiment, 4) simulate the situation of crime; perform special tasks for the disclosure of criminal activity or criminal organization; tacit obtaining samples, necessary for comparative studies.Variety forth in Chapter 21 of secret investigative (search) actions required by their scientific classification, which can be carried out according to the following criterias: depending on the possibility of intervention in private communication during it`s proceedings; depending on the severity of the offense under the investigation which might be conducted; depending on the official who decides to hold secret investigative (search) actions; depending on the type of results that can be obtained as a result of their conduct; depending on the capabilities (and appropriate) use confidential cooperation in the form of attracting confidant (ing) to conduct secret investigative (search) actions; etc. Classification of secret investigative (search) actions can be carried out also for other reasons, if they have a criminal procedure or criminalistics importance.

На підставі результатів аналізу положень глави 21 Кримінального процесуального кодексу України, підзаконних нормативно-правових актів, точок зору науковців та практиків, висвітлених в наукових джерелах, у статті здійснено спробу розробити класифікацію негласних слідчих (розшукових) дій. Встановлено низку проблемних аспектів щодо віднесення певних негласних слідчих (розшукових) дій до тієї чи іншої класифікаційної групи.
ЩОДО КЛАСИФІКАЦІЇ НЕГЛАСНИХ СЛІДЧИХ (РОЗШУКОВИХ) ДІЙ
Keywords: secret investigative (search) actions; affecting private communication; the Criminal Procedure Code of Ukraine; негласні слідчі (розшукові) дії; втручання у приватне спілкування; Кримінальний процесуальний кодекс України